(untitled) (European Journal of Economics, Finance and Business Development, 2023)
The article discusses the role and importance of the attractiveness of the investment environment in the socio-economic development of the regions of our republic, the existing problems, analytical data, conclusions, suggestions and recommendations in this regard.